The Human Sense of Olfaction - Walliczek-Dworschak, Ute; Hummel, Thomas (Facial Plastic Surgery, 2017)
The sense of olfaction is important not only for the detection of potential dangers such as fire or spoilt food, but also for the quality of life of human beings. In this article, we review the characteristics of the sense of smell and give a short overview about possible olfactory dysfunctions and their therapy.
Keywords: olfaction; smell; olfactory disorders; characteristics